Supplying a desert garrison. Pottery from the Roman fort at Gheriat el-Garbia (Libya) - Weber, Meike; Schmid, Sebastian (Rei Cretariae Romanae Fautorum Acta, 2012)
The Roman fort at Gheriat el-Garbia, approx. 280 km south of modern Tripoli, was established under Septimius Severus as part of the Roman frontier in Libya, the Limes Tripolitanus. It represents the largest Severan military site along this desert frontier. A vexillation of legio III Augusta from Lambaesis was stationed at the fort until AD 238. Henceforward Gheriat el-Garbia was supposedly the headquarters of the praepositus limitis (regionis) Tripolitanae until the last quarter of the 3rd century AD when the garrison finally abandoned the fort.